A Arqueologia da Guerra na Antiguidade Tardia - Gonçalves, Bruna Campos (Romanitas - Revista de Estudos Grecolatinos, 2015)
Resenha de: SARANTIS, A; CHRISTIE, N. (Ed.). War and warfare in Late Antiquity: current perspectives. Leiden: Brill, 2013. 1120 p. 2 v.